2015
DOI: 10.1016/j.devcel.2014.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 Mediates Bmp-Induced Sprouting Angiogenesis through Fmnl3-Driven Assembly of Endothelial Filopodia in Zebrafish

Abstract: During angiogenesis in vivo, endothelial cells (ECs) at the tips of vascular sprouts actively extend filopodia that are filled with bundles of linear actin filaments. To date, signaling pathways involved in the formation of endothelial filopodia have been studied using in-vitro-cultured ECs that behave differently from those in vivo. Herein, we have delineated a signaling pathway that governs the assembly of endothelial filopodia during angiogenic sprouting of the caudal vein plexus (CVP) in zebrafish. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
131
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(146 citation statements)
references
References 32 publications
11
131
3
1
Order By: Relevance
“…Again, weaker binding was found for GTP-Rac1 with about a fourfold enrichment over GDP-Rac1 ( Figure 4C; quantified in Figure 4E). These findings are consistent with human FMNL1/2 or zebrafish Fmnl3 activation by Cdc42 (Block et al 2012;Kuhn et al 2015;Richards et al 2015;Wakayama et al 2015) and mouse Frl1/Fmnl1 showing a weak preference for Rac-GTP over Rac-GDP, although the latter failed to bind Cdc42 (Yayoshi-Yamamoto et al 2000).…”
Section: Frl Is Regulated By Cdc42 In Vivosupporting
confidence: 79%
“…Again, weaker binding was found for GTP-Rac1 with about a fourfold enrichment over GDP-Rac1 ( Figure 4C; quantified in Figure 4E). These findings are consistent with human FMNL1/2 or zebrafish Fmnl3 activation by Cdc42 (Block et al 2012;Kuhn et al 2015;Richards et al 2015;Wakayama et al 2015) and mouse Frl1/Fmnl1 showing a weak preference for Rac-GTP over Rac-GDP, although the latter failed to bind Cdc42 (Yayoshi-Yamamoto et al 2000).…”
Section: Frl Is Regulated By Cdc42 In Vivosupporting
confidence: 79%
“…In summary, although Mogat1 expression is highly upregulated in fatty livers of lipodystrophic ( Agpat2 Ϫ / Ϫ ) and ob / ob oligonucleotide approaches in an acute experimental setting bring about reduced liver TAG and improved IR and type 2 diabetes mellitus . A recent study, although not related to the metabolic studies discussed here, reported that the use of antisense technology and genetic deletion resulted in widely different phenotypes (33)(34)(35). We interpret our study with an additional caution.…”
Section: Mogat1contrasting
confidence: 41%
“…For knockdown of tuba and cdc42, three antisense morpholino (MO) oligonucleotides that block translation or splicing were designed, targeting the ATG start codon or a splice donor site of exon 5 in tuba, and purchased from Gene Tools, LLC: tuba AUG MO (5Ј-ACCACCGAGCCAGCCTC-CATGTTCA-3Ј), tuba splice site MO (5Ј-AGCTGGG ATT-TACAGACCTGTTTCT-3Ј), and cdc42 AUG-MO (5Ј-CAAC-GACGCACTTGATCGTCTGC AT-3Ј). Knockdown of two control GEFs, Obscurin and Fgd5, was performed using the splice site morpholinos (25,26). The scrambled control oligo purchased from Gene Tools was used as a negative control, and the total amount of MO injected under each condition was kept equivalent for the control MOs.…”
Section: Methodsmentioning
confidence: 99%
“…4F). To ensure specificity of the tuba MOs, we additionally performed a side-by-side morpholino analysis targeting two other GEFs, Obscurin and Fgd5, which are not known to be involved in the Cdc42-mediated ciliogenesis pathway (25,26), in addition to the scrambled control MOs (Fig. 4F).…”
Section: Tuba Localizes To Ciliated Organs and Depletion Of Tuba Caumentioning
confidence: 99%